The use of Microscope Flash Media in Biology Laboratory Works - Herlina, Lina; Prasetya, Dheny (Journal of Biology Education, 2017)
This research aims to optimize the learning activities and test the effectiveness of the use of flash media microscope in biology lab. Research using a design research and development that includes four stages, namely field observations, the implementation of media development, media validation, and implementation of the pilot (small scale and large scale). Small-scale trials were conducted at SMAN 5 Magelang class XI MIA-1 and large-scale trials were conducted at SMAN 5 Magelang XI MIA-1 and XI MIA-3 classes. Validation results from media experts and microscopes experts were 82% and 69%, respectively, with good criteria. The results of the small-scale trials showed a positive response to the flash media using the microscope, while the large scale trials showed results of 82% of students with criteria skilled in using a microscope. The result of questionnaire of student responses shows very good criteria to flash media learning of microscope usage and good on all aspect asked, while teacher give very good response. Based on the results of research ,it is concluded that the use of microscope flash media developed feasible in optimizing the activities of Biology lab works.